If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x=-4x-12
We move all terms to the left:
8x-(-4x-12)=0
We get rid of parentheses
8x+4x+12=0
We add all the numbers together, and all the variables
12x+12=0
We move all terms containing x to the left, all other terms to the right
12x=-12
x=-12/12
x=-1
| 27^x+3=27^x+3 | | 19=3m-2 | | 24x(24-x)=2880 | | 27^x+3=9^x+3 | | 7/8y-11=-4 | | 18=8m-6 | | 2/3w-1=-2/3 | | 27^x+3=9 | | 2+38=-5(5x-8) | | 3x^2+2x−20=2x^2+15 | | 14+x=42;x=32 | | -13+10=-3(x+5) | | -179=7(7-5p)-3p | | 3=6n+9 | | 44+(x+10)=180 | | 4(x+6)-5=19 | | -2x-8=-14 | | -1.3=y/3+3.5 | | 15+1=-4(8x-4) | | -2x–8=-14 | | 5y-3y=3y+5 | | 4÷(y-7)=5 | | 2(4x+6)=-47+27 | | 4+3(2x-3)=6x-5 | | 8x+40=6x=12 | | 5(3x+8)=-41+6 | | 2x+(-11)+73=180 | | 2x+-11)+73=180 | | x-27=8+18 | | (-8y-12y)=9 | | (2x+5)=(5x+28) | | 2x+5x=21+7 |